2018
DOI: 10.1093/jamia/ocy002
|View full text |Cite
|
Sign up to set email alerts
|

Designing risk prediction models for ambulatory no-shows across different specialties and clinics

Abstract: ObjectiveAs available data increases, so does the opportunity to develop risk scores on more refined patient populations. In this paper we assessed the ability to derive a risk score for a patient no-showing to a clinic visit.MethodsUsing data from 2 264 235 outpatient appointments we assessed the performance of models built across 14 different specialties and 55 clinics. We used regularized logistic regression models to fit and assess models built on the health system, specialty, and clinic levels. We evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 30 publications
3
51
0
Order By: Relevance
“…For that, it imposes a penalty on the model β coe cients to induce dispersion, such that coe cients of less relevant predictors are reduced to zero [17]. This process results in biased coe cient estimates that can no longer be interpreted as odds ratios, as in a logistic regression, but rather as a weight or relative importance of the predictor variable [18]. The best value for the penalty parameter λ is the one that leads to the smallest mean square error (MSE) in the cross validation.…”
Section: Logistic Regression With Lasso Penalization (Least Absolute mentioning
confidence: 99%
See 1 more Smart Citation
“…For that, it imposes a penalty on the model β coe cients to induce dispersion, such that coe cients of less relevant predictors are reduced to zero [17]. This process results in biased coe cient estimates that can no longer be interpreted as odds ratios, as in a logistic regression, but rather as a weight or relative importance of the predictor variable [18]. The best value for the penalty parameter λ is the one that leads to the smallest mean square error (MSE) in the cross validation.…”
Section: Logistic Regression With Lasso Penalization (Least Absolute mentioning
confidence: 99%
“…No-show rates may vary from 3-80% in healthcare systems, depending on the service being provided and patients' demographic characteristics [4]. Studies report different no-show rates; e.g., 18.80% in a study carried out in a medical center offering consultation on 10 different ambulatory specialties [4], 21.90% in bariatric surgery appointments in a specialized clinic -considering only consultations before and after surgery [2], and 6.50% in a radiology department considering all exams performed [3]. In the Brazilian public health network, patient no-show has become a chronic problem, similar to what is observed in other countries.…”
Section: Introductionmentioning
confidence: 99%
“…They also proposed a stacking model by using logistic regression as the meta-classifiers and three algorithms of random forests, artificial neural networks, and stochastic gradient boosting as the base-learners. Ding et al (2018) used regularized logistic regression to build predictive models using datasets from different specialties and clinics. They concluded that, in almost all specialties, the appointments rescheduled by the provider were the most important predictor of patient no-shows.…”
Section: Review Of Patient No-show Research Papersmentioning
confidence: 99%
“…Kalb et al (2012) and Mohammadi et al (2018) considered a late cancellation as a no-show if the patient canceled the appointment within 24 hours before the appointment date. Ding et al (2018) considered cancellations on the day of the appointment as no-shows. Topuz et al (2018) and Srinivas and Ravindran (2018) considered a late cancellation as a missed appointment if the patient canceled the appointment within eight hours and 72 hours before the appointment date, respectively.…”
Section: Review Of Patient No-show Research Papersmentioning
confidence: 99%
See 1 more Smart Citation